Modeling of BMI index and leg angles during tractors’ clutching on Gastrocnemius muscle using Genetic Algorithm - H Fallahi; M Hossein Abbaspour-Fard; A Azhari; M Khojastehpour; A Nikkhah; A Rohani (Salāmat-i kār-i Īrān, 2016)
Backgrond and aims: Due to the rapid development of agricultural mechanization operations and the use of tractor as one of the most important agricultural machinery, focus on the health, ergonomic and safety working conditions of the tractor operators is a MUST.